The virtual executive [ how to act like a CEO online and offline - Benton, D. A. [ (Debra A.)] (McGraw-Hill, 2012)
Teaches you about the things you need to know to navigate seemingly endless choices of social media and virtual communication tools in order to stay relevant in a sea of competition. From videoconferencing, instant messaging, and webinars to LinkedIn, Facebook, and Twitter, this title explains how and when to use each platform